Fuel efficiency improvements - feedback mechanisms and distributional effects in the oil market - Finn Roar Aune; Ann Christin Bøeng; Snorre Kverndokk; Lars Lindholt; Knut Einar Rosendahl (Statistics Norway, Research Department, 2016)
We study the interactions between fuel efficiency improvements in the transport sector and the oil market, where the efficiency improvements are policy-induced in certain regions of the world We are especially interested in feedback mechanisms of fuel efficiency such as the rebound effect, carbon leakages and the "green paradox", but also the distributional effects via oil price changes for different regions, sectors and oil producers. An intertemporal numerical model of the international oil market is introduced, where OPEC-Core producers have market power. We find that the rebound effect has a noticeable effect on the transport sector, but also on other sectors through lower oil prices in the regions that introduce the policy. There is a small green paradox effect in the sense that oil consumption increases initially when the fuel efficiency measures are gradually implemented. Finally, there will be significant carbon leakages if the policy is not implemented in all regions, with leakage rates of 35 per cent or higher. Non-OPEC producers will suffer more than OPEC producers by fuel efficiency policies due to high production costs.
Keywords: D42; Q54; R48; 330; Fuel efficiency; transport; oil market; market power; distribution: feedback mechanisms